Increased freezing and decreased positive affect in postinstitutionalized children. (30th July 2013) - Stellern, Sarah; Esposito, Elisa; Mliner, Shanna; Pears, Katherine; Gunnar, Megan
<x xml:space="preserve">Abstract</x> Background Early neglect is associated with increased risk of internalizing disorders in humans and with increased fear behavior in animals. When children are adopted out of orphanages in which they experienced institutional neglect, anxiety and depressive disorders often are not seen until adolescence. What has not been examined is whether even young children adopted from institutional care exhibit heightened fear or behavioral inhibition. Method Children adopted between 15 and 35 months from institutional care were examined twice during their first year postadoption and compared with children of the same age reared in their birth families. A modified version of the Laboratory Temperament Assessment Battery for Preschoolers was used with the children being exposed to two mechanical toys designed to be highly arousing and fear eliciting. Because children in institutions tend to exhibit low levels of positive affect, the children were also examined during exposure to two positive stimuli. Sessions were videotaped and coded by observers blind to the study purpose. Results Postinstitutionalized children froze more in fear vignettes and were less positive in both fear and positive vignettes than nonadopted children. Group differences did not diminish significantly from the first session to the next, 6 months later. Conclusions Children exposed to early institutional neglect exhibit emotional biases that are consistent with their previously demonstrated risk for the development of internalizing disorders.